Effect of Burkholderia ambifaria LK-P4 inoculation on the plant growth characteristics, metabolism, and pharmacological activity of Anoectochilus roxburghii - Wang, Juanying; Zhao, Hanyu; Chen, Ting; Lin, Wenxiong; Lin, Sheng (Frontiers in Plant Science, 2022)
Plant growth-promoting bacteria (PGPB) represents a common biological fertilizer with remarkable effect in improving crop production and environmental friendliness. In the present work, we presented a detailed characterization of plant morphology and physiology, metabolism, and pharmacological activity of A. roxburghii between Burkholderia ambifaria LK-P4 inoculation and un-inoculation (CK) treatment by routine analytical techniques (include microscopy and enzymatic activity assays and so on) coupled with metabolomics approaches. The results from morphology and physiology showed that P4 bacteria could significantly increase plant stomatal density, fresh weight, survival rate and the content of total flavonoids in leaves but reduce the amount of free amino acid. Furthermore, metabolite data showed that fatty acids (linoleic acid, linolenic acid, stearic acid) and active substance (kyotorphin and piceatannol) were specifically up-regulated in P4 inoculation. It was also demonstrated that the differential metabolites were involved in citrate cycle, glyoxylate and dicarboxylate metabolism, and biosynthesis of unsaturated fatty acids pathway. In addition, pharmacological efficacy found that A. roxburghii under P4 inoculation can significantly decrease (p < 0.05) blood glucose levels and protect the organs of mice with similar effect of Glibenclamide tablets. Overall, it can be seen that the exogenous P4 bacteria can promote the growth and increase content of special metabolites in A. roxburghii. This study provided theoretical basis and supported for the high-yield and high-quality bionic cultivation of A. roxburghii.